Women entrepreneurship: challenges and work-life balance / Nurul Hayani Abd Rahman ... [et al.] - Abd Rahman, Nurul Hayani; Mohamed Isa, Zuraidah; Shafie, Nani Ilyana (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The involvement of women in entrepreneurship needs to be supplemented with support from a spouse, family, friends, and entrepreneurial support systems. Women who decided to conduct entrepreneurial activities should have a strong spirit to face challenges so that they can achieve entrepreneurial success. These challenges sometimes lead to a good work-life balance. Challenges are also referred to as obstacles, barriers, conflicts, and problems faced by women entrepreneurs in every economic sector. Ilhaamie, Siti Arni, Rosmawani, and Hassan Al-Banna (2014) reported that the most prevalent type of challenges faced by Muslim women entrepreneurs in Malaysian small and medium enterprises (SMEs) are lack of finance, low demand, and location issues.